CARACTÃ‰RISTIQUES MORPHOLOGIQUES ET GÃ‰OCHIMIQUES DES MANTEAUX Dâ€™ALTÃ‰RATION DÃ‰VELOPPÃ‰S SUR GRANITOÃDES DANS LA RÃ‰GION DE Lâ€™ADAMAOUA (CAMEROUN) - Souaibou, Souaibou; Ondoa, J. Mvondo; Elimbi, A.; Ekodeck, G.-E.; Kamgang, V.-K.-B. (European Scientific Journal, ESJ, 2015)
Seven samples of rocks, including three parent rock and four weathered rock from Wack (Vina division, Adamawa Region, Cameroon) have been studied. According to chemical analysis and chemical weathering indices calculated, weathering rocks conserve the structure of parent rocks. During weathering and the influence of the steep slope, the chemical elements are completely disorganized. The quantitative determination of the degree of chemical weathering of these rocks based on whole rock chemistry was performed. The slope of the straight regression absolute value is closed to 1. These various chemical weathering indices calculated has shown that they are significantly related.